Is Genistein a Threat to Male Reproductive Potential? - Yashechkina, Tatiana (2017)
Genistein is one of the most abundant phytoestrogens in soybeans. Because of its chemical similarity to endogenous estrogens, genistein can bind to estrogen receptors (ERs) present in cells and mediate an estrogenic response. Its estrogenic action may potentially interfere with normal functioning of various systems in the human organism, including the reproductive system which is highly regulated by sex hormones. The increasing interest in using genistein for treatment and prevention of diseases such as cancer, osteoporosis, cardiovascular diseases, relief of menopause symptoms, among others. As well as the increasing consumption of soy in Western populations as a substitute for animal protein and its use to produce food for infants are worrisome factors because the effects of phytoestrogens on the human organism are still a matter of intense debate. Animal studies are contradictory and human studies are scarce. The aim of the present study was to evaluate genistein safety on human Sertoli cells (hSCs) in vitro. These cells are pivotal for successful espermatogenesis since they provide nutritional and physical support to sperm germ cells. Biopsies from six patients, with conserved espermatogenesis, were chosen at an infertility clinic and primary cultures of human Sertoli cells were cultured and maintained until reaching confluence. Then they were treated with different genistein concentrations during 24h. Different citotoxicity test were perfomed. No disturbances were found in hSCs treated with genistein. Therefore, we conclude that this compound is not cytotoxic to these cells. Subsequently, the analysis of one of the most relevant metabolic pathways, glycolysis, in these cells was made, which originates pyruvate, that in turn, later, is used for the production of lactate. This substrate is an important energy source for germ cells. However, the absorption and excretion of different metabolites of this pathway, in addition to the enzymatic activity of lactate dehydrogenase, did not show significant variations after exposure of hSCs to genistein. Also genistein influence on oxidative stress rates in hSCs was evaluated, since reactive oxigene species (ROS) production is common during cell metabolism and if not eliminated efficiently it can cause irreversible damage on different cell structures and may even lead to cell death. The results of this study demonstrate that genistein did not influence oxidative stress rates. Alltoghether, we can conclude that no harmfull effects, on the parameters analyzed, were caused by genistein on hSCs. Altough it does not mean that genistein, and other phytoestrogens, are safe for the remaining of the reproductive system more studies regarding this subject are needed for a better understanding of their mechanisms of action.